Seasonal Distribution, Blood-Feeding Habits, and Viruses of Mosquitoes in an Open-Faced Quarry in Connecticut, 2010 and 2011 - Anderson, John F; Armstrong, Philip M; Misencik, Michael J; Bransfield, Angela B; Andreadis, Theodore G; Molaei, Goudarz (Journal of the American Mosquito Control Association, 2018)
Seasonal abundance of mosquitoes, their viruses, and blood–feeding habits were determined at an open-faced quarry in North Branford, CT, in 2010 and 2011. This unique habitat had not previously been sampled for mosquitoes and mosquito-borne viruses. Thirty species of mosquitoes were identified from 41,719 specimens collected. Coquillettidia perturbans, Aedes trivittatus, and Ae. vexans were the most abundant species and represented 34.5%, 17.7%, and 14.8% of the totals, respectively. Jamestown Canyon virus was isolated from 6 species of mosquitoes collected from mid-June through July: Cq. perturbans (3 pools), Ae. cantator (3), Ae. trivittatus (2), Ae. aurifer (1), Ae. excrucians (1), and Culex pipiens (1). West Nile virus was cultured from 8 pools of Cx. pipiens and from 1 pool of Culiseta melanura collected from mid-August through late September. Cache Valley virus was isolated from 4 species of mosquitoes in 3 genera from about mid-August through late September 2011: Cq. perturbans (5 pools), Ae. trivittatus (2), Anopheles punctipennis (1), and An. quadrimaculatus (1). Nine different mammalian hosts were identified as sources of blood for 13 species of mosquitoes. White-tailed deer, Odocoileus virginianus, were the most common mammalian hosts (90.8%), followed by raccoon, Procyon lotor (3.1%), coyote, Canis latrans (2.4%), and human, Homo sapiens (1.2%). Exclusive mammalian blood-feeding mosquitoes included: Ae. canadensis, Ae. cantator, Ae. excrucians, Ae. japonicus, Ae. vexans, An. punctipennis, and Cx. salinarius. Fourteen species of birds, mostly Passeriformes, were identified as sources of blood from 6 mosquito species. Five species that fed on mammals (Ae. thibaulti, Ae. trivittatus, Ae. cinereus, Cq. perturbans, and Cx. pipiens) also fed on birds.